KARAKTERISTIK ARUS LAUT DI PELABUHAN PANTOLOAN KOTA PALU SULAWESI TENGAH - Ayusari Wahyuni; Sri Ningsih; Rahmaniah Rahmaniah (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2020)
Port construction at Pantoloan has influenced the condition of port and its environment. The hidro-oceanography process has influenced the condition of water, especialy to the current. This research was aimed to know the characteristic of current at Pantoloan, Palu, Central Sulawesi. The method used in this research was the measurement of current using a Floater. Data analysis of the floater current and position or coordinates of the floater were recorded on GPS. The results showed that the average of current velocity at high tide at the study site was 0.176 m/s with 221° to the to the Southwest and the average of the current speed at low tide was 0.178 m/s with 310° from the north to the northwest. Current speed at low tide is relatively weak compared to current speed at high tide.